The machinery of criminal justice - Bibas, Stephanos (New York ; Oxford : Oxford University Press, 2012)
Presenting a survey of how the legal process in the US has changed over two centuries, this text calculates the social cost of a prevailing quest for efficiency that has seen both courts and corrections removed from public control & placed in the hands of professionals.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Criminal justice, Administration of -- United States